Initiating pedogenesis of magnetite tailings using Lupinus angustifolius (narrow-leaf lupin) as an ecological engineer to promote native plant establishment - Zhong, Hongtao; Lambers, Hans; Wong, Wei San; Dixon, Kingsley; Stevens, J.C.; Cross, Adam (2021)
Mine tailings pose physical and chemical challenges for plant establishment. Our aim was to learn from natural processes in long-term soil and ecosystem development to use tailings as novel parent materials and pioneer ecological-engineering plant species to ameliorate extreme conditions of tailings, and facilitate the establishment of subsequent native plants. A glasshouse trial was conducted using magnetite tailings containing various amendments, investigating the potential of the nitrogen (N)-fixing, non-native pioneer species Lupinus angustifolius (Fabaceae), narrow-leaf lupin, as a potential eco-engineer to promote soil formation processes, and whether amendment type or the presence of pioneer vegetation improved the subsequent establishment and growth of 40 species of native plants. We found that L. angustifolius eco-engineered the mine tailings, by enhancing the N status of tailings and mobilising primary mineral P into organic P via a carboxylate-exudation strategy, thereby enabling subsequent growth of native species. The substantial increases of the soil organic P (from ca. 10 to 150 mg kg−1) pool and organo-bound Al minerals (from 0 to 2 mg kg−1) were particularly evident, indicating the initiation of pedogenesis in mine tailings. Our findings suggest that the annual legume L. angustifolius has eco-engineering potential on mine tailings through N-fixation and P-mobilisation, promoting the subsequent growth of native plants. We proposed Daviesia (Fabaceae) species as native species alternatives for the non-native L. angustifolius in the Western Australian context. Our findings are important for restoration practitioners tasked with mine site restoration in terms of screening pioneer eco-engineering plant species, where native plants are required to restore after mine operations.